Investigation of the Relationship between Entrepreneurial Opportunity Recognition and Entrepreneurial Capitals - Ramezanpour, Susan; Amiriyan, Seyran; Shirazi, Ali Naghi Mosleh (International Journal of Asian Social Science, 2014)
The heart of entrepreneurship is the creation and/or recognition of opportunities. Although there is no universal definition of entrepreneurship, opportunity recognition has been viewed as the central definition of this phenomenon. Without an opportunity there is no entrepreneurship. Therefore opportunity recognition is widely seen as a key step of the entrepreneurial processes. The identification of opportunities has been recognized as one of the most important abilities of successful entrepreneurs. The goal of this study is to examine the relationship between the entrepreneurial opportunity recognition process and the social, human capital. The entrepreneurship model utilized in this study is the one following the resource-based theory. In the framework of the present study a total of 353 questionnaires were distributed among Iranian entrepreneurs and the data were analyzed based on multi variety regression and path analysis. The obtained results from data analyses show that the process of opportunity recognition among Iranian entrepreneurs is dependent upon social and human capitals.